2015
DOI: 10.1183/13993003.01558-2014
|View full text |Cite
|
Sign up to set email alerts
|

CC-chemokine ligand 2 inhibition in idiopathic pulmonary fibrosis: a phase 2 trial of carlumab

Abstract: The objective of this study was to determine the safety and efficacy of carlumab in the treatment of idiopathic pulmonary fibrosis (IPF).A phase 2, randomised, double-blind placebo-controlled dose-ranging study was conducted in patients with IPF (n=126). Patients were randomised to carlumab (1 mg·kg −1 , 5 mg·kg, or 15 mg·kg −1 ) or placebo every 4 weeks. The primary endpoint was the rate of percentage change in forced vital capacity (FVC). Secondary endpoints were time to disease progression, absolute change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 34 publications
2
68
0
1
Order By: Relevance
“…Notably, a phase II trial in IPF (NCT00786201) using a human monoclonal antibody to CCL2 (MCP-1) showed no effect on disease progression, pulmonary function parameters, or mortality. However, free CCL2 levels remained elevated above baseline in subjects in this trial, suggesting pharmacologic failure of this particular therapeutic agent (39). Thus, further studies will be needed to determine whether the CCL2/CCR2 axis can be effectively targeted in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a phase II trial in IPF (NCT00786201) using a human monoclonal antibody to CCL2 (MCP-1) showed no effect on disease progression, pulmonary function parameters, or mortality. However, free CCL2 levels remained elevated above baseline in subjects in this trial, suggesting pharmacologic failure of this particular therapeutic agent (39). Thus, further studies will be needed to determine whether the CCL2/CCR2 axis can be effectively targeted in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of decline in FVC was the most common primary outcome end-point in recent clinical trials in IPF, expressed either in millilitres per year [47] or as percentage of the predicted value [115][116][117]. It is currently debated whether change in FVC over time is the optimal outcome for clinical trials in IPF.…”
Section: Lung Function Indices As Indicators Of Prognosis and Outcomementioning
confidence: 99%
“…In particular, in a recent study targeting of CCR2 + signalling with a non-specific CCL2 monoclonal antibody did not improve the clinical outcomes of IPF patients, with an unexpected increase in free CCL2 levels in patients receiving active treatment 12. The authors of that study hypothesised that this might in part be due to compensatory excess release of free CCL2 12. However, it is also possible that the lack of clinical benefit from the CCL2 monoclonal antibody might be because untargeted treatments not only eliminate disease promoting CCR2 + cell populations, but also those that potentially limit disease progression.…”
Section: Discussionmentioning
confidence: 95%
“…In particular, in a recent study targeting of CCR2 + signalling with a non-specific CCL2 monoclonal antibody did not improve the clinical outcomes of IPF patients, with an unexpected increase in free CCL2 levels in patients receiving active treatment 12. The authors of that study hypothesised that this might in part be due to compensatory excess release of free CCL2 12.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation